Simplify
2 3 − 6 6 − 4 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i solved it with imagined it in mind
Log in to reply
seriously ? congratz ^_^
aha..nice solution
6-4*sqrt(2) can never be equal to (2-sqrt(2))^2
Log in to reply
Its not 6-4*sqrt(2) is square of 2-sqrt(2)
It is equal to it, don't you know maths ?
Wow! well-layered out solution
I was correct.....Yahoooo!!!!
I would like to know the practical application of square roots and cube roots. Why are we taught this at the school level? How can we perform an activity on square roots and cube roots so as to easily understand it?
Log in to reply
simpler problem with one square root to empower future mathematicians..... and check understanding of square roots and exponents in general.
depends on each person, because if you are studying for the exact area at the college roots will follow you
Log in to reply
I would like to know the practical applications at school level.
Did the same way.
I would let K equal to the equation, keeping in mind that it is going to be a+(b)^(1/n), then rewrite evertying with prime factorization simplify and solve for K.
3+\sqrt{3}
magnificent simplification
wow. that was a nice trick! thanks for the solution
i simply calculated it.
Working from the inner root... Sq.root(6-2.root2)=sq.root[(2)^2+(root2)^2-2.2.root2]=sq.root(2-root2)^2=(2-root2)..next we have sq.root(11+3root2) which in similer way turns out to be 3+root(2)
Olympiad problems are much more difficult
Innermost sqr is smaller than one
Entire inner expression is 20ish
Solution is (most probably) 4 something
first make 6-4X2^1/2 in the form of a^2 +b^2-2ab which makes it (2-2^1/2)^2. Under the square root, it becomes 2-2^1/2. Using the same principle, the rest of the sum can be solved.
Excellent.
6-4((2)^(1/2)) =(2-(2)^(1/2))^2 and then the relation becomes=(11+6 2^(1/2))= 9+2+(6 2(1/2)) so solution is 3+2^(1/2)
Problem Loading...
Note Loading...
Set Loading...
We work from the inner square root. We guess that 6 − 4 2 is a perfect square of the form a + b c . Since
6 − 4 2 = ( a + b c ) 2 = a 2 + b 2 c − 2 a b c ,
we see that 6 = a 2 + b 2 c , − 4 = − 2 a b , 2 = c . This gives us a = 2 , b = − 1 , c = 2 . Hence 6 − 4 2 = ( 2 − 2 ) 2 . Since 2 − 2 > 0 , thus 6 − 4 2 = ( 2 − 2 ) .
In a similar manner, we guess that the outer square root 2 3 − 6 ( 2 − 2 ) = 1 1 + 6 2 also has the form x + y z . Since
1 1 + 6 2 = ( x + y z ) 2 = x 2 + y 2 z + 2 x y z ,
we see that 1 1 = x 2 + y 2 z , 6 = 2 x y , 2 = z . Then, 2 3 − 6 6 − 4 2 = 2 3 − 6 ( 2 − 2 ) = 1 1 + 6 2 = ( 3 + 2 ) 2 Hence, the expression is equal to 3 + 2 . This gives us x = 3 , y = 1 , z = 2 , hence 1 1 + 6 2 = ( 3 + 2 ) 2 . Since 3 + 2 > 0 , hence the answer is 3 + 2 .